Forkhead Transcription Factor FOXO1 Is Regulated by Both a Stimulatory Thyrotropin Receptor Antibody and Insulin-Like Growth Factor-1 in Orbital Fibroblasts from Patients with Graves' Ophthalmopathy - Kumar, Seema (Thyroid, 2015)
Background: Activation of thyrotropin receptor (TSHR) and/or insulin-like growth factor (IGF-1) receptor (IGF-1R) enhances HA production and adipogenesis in orbital fibroblasts from patients with Graves' ophthalmopathy (GO) and recapitulates the tissue remodeling characteristic of the orbit in GO. A functional relationship between TSHR and IGF-1R has long been postulated, and recently bidirectional crosstalk between the receptors in GO fibroblasts was demonstrated. Because the transcription factor Forkhead box O-1 (FOXO1) was recently shown to be a critical downstream mediator of TSH and IGF-1 effects on thyrocyte proliferation, studies were designed to determine whether FOXO1 might similarly act as a common mediator of M22, a stimulatory TSHR antibody (TSAb), and IGF-1 in GO orbital fibroblasts. Methods: FOXO1 mRNA and protein were measured in orbital tissue specimens derived from normal individuals and patients with GO. In addition, the control of FOXO1 cellular localization was investigated using quantitative Western blotting of fractionated cell lysates from orbital fibroblasts treated with M22 and/or IGF-1 with or without specific TSHR, IGF-1R, or PI3K/AKT1/2 inhibitors. Results: Significantly lower levels of both FOXO1 mRNA and protein were found in GO orbital tissue specimens compared with normal orbital tissues (M = 39%, p = 0.043; M = 46.4%; p = 0.028, respectively). In addition, treatment of GO orbital cultures with M22, IGF-1, or M22 plus IGF-1 increased cytoplasmic FOXO1 compared with control (1.63-fold, p = 0.008; 1.68-fold, p = 0.001; 1.61-fold, p ≤ 0.001, respectively) and decreased nuclear FOXO1 (M = 28%, p = 0.002; M = 38%, p ≤ 0.001; M = 35%, p = 0.007, respectively). These effects were inhibited by co-treatment with the respective, but not the opposite, receptor antagonist. AKT inhibition of M22 or IGF-1-treated cultures was found to increase nuclear (1.4-fold, p = 0.026; 1.3-fold, p = 0.001, respectively) and decrease cytoplasmic (24.2%, p = 0.001; 36%, p = 0.004, respectively) FOXO1 localization. Conclusions: These data point to FOXO1 as an important mediator of TSAb and IGF-1 action via their cognate receptors in GO orbital fibroblasts. These findings provide a link between the low FOXO1 protein levels demonstrated in GO orbital tissue and the tissue remodeling characteristic of GO, and suggest novel therapy for GO aimed at increasing nuclear expression of FOXO1 in GO target cells.